The Benefits of Technology in Islamic Religious Education - Kumaidi, Muhamad; Febriani, Evi; Aisy, Azahra Rahdatull (Education Achievement: Journal of Science and Research, 2024)
Urgency to Utilise To achieve autonomous Islamic learning and education programmes, technology is used in Islamic education. This page seeks to answer questions about the utilisation of technology in Islamic education, the platforms used, and the degree to which the use of technology is important or not. The writing of this article uses a qualitative type of research. This research aims to find out how educational technology helps the assimilation of Islamic Religious Education in the classroom. By using the methodology of literature study and interviews, the author used qualitative research methodology. The results show that technology has an important role in facilitating communication between parents, teachers and children during the pandemic. Technology makes learning easier by removing the requirement of face-to-face interaction. Various services, including Zoom Cloud Assembly, Google Meet, Google Study Room, and WhatsApp, can be used to exchange educational resources. Desk research method Applications such as Apps like Canva, Toontastic, Lectora, KineMaster, Powtoon, Prezi, Wondershare Filmora, and Sigil can help educators create Islamic educational media. As students today face different challenges than in the past, integrating technology into the teaching and learning process is essential.